2021
DOI: 10.3390/life11121352
|View full text |Cite
|
Sign up to set email alerts
|

Credibility of the Neutrophil-to-Lymphocyte Count Ratio in Severe Traumatic Brain Injury

Abstract: Traumatic brain injury (TBI) is one of the leading causes of morbidity and mortality worldwide. The consequences of a TBI generate the activation and accumulation of inflammatory cells. The peak number of neutrophils entering into an injured brain is observed after 24 h; however, cells infiltrate within 5 min of closed brain injury. Neutrophils release toxic molecules including free radicals, proinflammatory cytokines, and proteases that advance secondary damage. Regulatory T cells impair T cell infiltration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
(142 reference statements)
0
2
0
Order By: Relevance
“…For total cholesterol, it has been reported that it predicts increased length of hospital stays in patients with trauma [ 32 ] and that hypocholesterolemia is associated with mortality in patients with head trauma [ 33 ]. Although there are few reports on lymphocyte counts in general patients with trauma, in recent years, several reports have suggested that the neutrophil/lymphocyte ratio is an indicator of prognosis in patients with head injury [ 34 ]. In brain injury following ischemic stroke, lymphocytes are said to contribute to the repair of the brain tissue [ 35 ], and there are also reports of decreased lymphocyte counts in patients with head trauma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…For total cholesterol, it has been reported that it predicts increased length of hospital stays in patients with trauma [ 32 ] and that hypocholesterolemia is associated with mortality in patients with head trauma [ 33 ]. Although there are few reports on lymphocyte counts in general patients with trauma, in recent years, several reports have suggested that the neutrophil/lymphocyte ratio is an indicator of prognosis in patients with head injury [ 34 ]. In brain injury following ischemic stroke, lymphocytes are said to contribute to the repair of the brain tissue [ 35 ], and there are also reports of decreased lymphocyte counts in patients with head trauma [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interferon gamma is mainly involved in immune regulation, and its expression level is associated with neurological diseases ( Zhang et al, 2020 ; Döhne et al, 2022 ; Wen et al, 2022 ). TBI could induce a serial of cytokines, including interferon gamma and activate various types of immune cells ( Siwicka-Gieroba and Dabrowski, 2021 ; Salem et al, 2022 ). A published study on status epileptics suggests that intraventricular injection of recombinant interferon gamma may reduce neuron damage on rat hippocampus ( Ryu et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%